Pathogenetic therapy in patients with COVID-19 - V. A. Kapatsina; M. A. Vashukova; D. A. Gusev (Журнал инфектологии, 2022)
The new coronavirus infection (COVID-19) has become a truly global challenge for all of humanity, and, above all, for the healthcare system. Among its most important aspects that require careful analysis are the clinical and laboratory features of the course of the disease, which make it possible to determine approaches to pathogenetic therapy in severe forms of the disease.Materials and methods. A retrospective analysis of the medical records of patients with severe COVID-19 who were hospitalized in St. Petersburg State Budgetary Infectious Diseases Clinical Hospital named after S.P. Botkin” in 20202022. Clinical and laboratory characteristics were assessed, including levels of C-reactive protein, interleukin-6, and fever dynamics. The criteria for prescribing drugs for pathogenetic therapy in patients with COVID-19 and their effectiveness were determined.Results. In the treatment of patients with COVID-19, it is necessary to carefully evaluate the clinical picture of the course of the disease, which is ahead of changes in laboratory parameters. The introduction of humanized antibody preparations leads to a regression of general infectious symptoms, subjective and objective manifestations of respiratory failure and, as a result, to a reduction in the length of stay of patients in the hospital. It is extremely important to timely preventive administration of drugs during the period of increasing “cytokine storm”. The optimal time for prescribing drugs is 1–3 days from the moment of receipt, until the patient is transferred to a ventilator.